Doubly Fed Induction Generator Open Stator Synchronized Control during Unbalanced Grid Voltage Condition - Akrama Khan; Xiao Ming Hu; Mohamed Azeem Khan; Paul Barendse (Energies, 2020)
In this paper, a systematic synchronization procedure is proposed for a doubly fed induction generator (DFIG) during unbalanced grid voltage conditions. The initial induced voltage at the open stator terminal is required to synchronize with the grid voltage in magnitude, frequency and phase. An open stator negative sequence rotor current controller is implemented with the conventional DFIG vector controller, which allows the induced stator voltage to become as unbalanced as the grid voltage, hence enabling a smooth connection. A brief comparison is provided for practical issues such as controller structure variation between DFIG open stator and normal operating conditions, and initial encoder rotor angle measurement offset. The procedure is validated experimentally on a 2.2 kW laboratory-scaled DFIG test bench.